MANAGERIAL OWNERSHIP MODERATING SUSTAINABILITY REPORTING AND PHILANTHROPY DISCLOSURE ON FIRM VALUE - Wulan Nurdiana Sari; Nofryanti; Iin Rosini (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to obtain empirical evidence regarding Managerial Ownership Moderating Sustainability Reporting and Philanthropy Disclosure on Firm Value. This study uses purposive sampling to determine the sample, with 62 companies as samples and a 3-year observation period from 2020 to 2022, resulting in 186 observational data points. The research data was obtained through the official websites of the Indonesia Stock Exchange and the respective companies' websites. Data analysis was conducted using E-Views with panel data regression analysis using the Fixed Effect Model. The research findings indicate that Sustainability Reporting affects company value, Philanthropy Disclosure has a negative impact on company value, Managerial Ownership does not moderate the relationship between Sustainability Reporting and company value, and Managerial ownership moderates the relationship between philanthropy disclosure and firm value.